Interspecies transfer of biosynthetic cobalamin for complete dechlorination of trichloroethene by Dehalococcoides mccartyi - Haijun Li; Shanming Wei; Na Liu; Yalu Du; Guantao Ding (Water Science and Technology, 2022)
Complete dechlorination of trichloroethene (TCE) by Dehalococcoides mccartyi is catalyzed by reductive dehalogenases (RDases), which possess cobalamin as the crucial cofactor. However, virtually all D. mccartyi isolated thus far are corrinoid auxotrophs. The exogenous addition of commercially available cobalamin for TCE-contaminated site decontamination is costly. In this study, TCE reduction by a D. mccartyi-containing microbial consortium utilizing biosynthetic cobalamin generated by interior corrinoid-producing organisms within this microbial consortium was studied. The results confirmed that subcultures without exogenous cobalamin in the medium were apparently unaffected and were able to successively metabolize TCE to nonchlorinated ethene. The 2-bromoethanesulfonate and ampicillin resistance tests results suggested that ampicillin-sensitive bacteria rather than methanogenic archaea within this microbial consortium were responsible for biosynthesizing cobalamin. Moreover, relatively stable carbon isotopic enrichment factor (ɛ-carbon) values of TCE were obtained regardless of whether exogenous cobalamin or selective inhibitors existed in the medium, indicating that the cobalamin biosynthesized by these organisms was absorbed and utilized by D. mccartyi for RDase synthesis and eventually participated in TCE reduction. Finally, the Illumina MiSeq sequencing analysis indicated that Desulfitobacterium and Acetobacterium in this microbial consortium were responsible for the de novo cobalamin biosynthesis to fulfill the requirements of D. mccartyi for TCE metabolism. HIGHLIGHTS TCE degradation to ETH via D. mccartyi-containing consortium without exogenous cobalamin is achieved.; Biosynthesized cobalamin facilitates stable ɛ-carbon values for TCE.; Bacteria rather than archaea in this consortium are potential cobalamin synthesizers.; Desulfitobacterium and Acetobacterium are responsible for cobalamin biosynthesis.;